Going for attractiveness and excellence : A cross-country review of excellence in apprenticeship in Austria, Denmark, Germany and Switzerland : Chapter 12 - Le Mouillour, Isabelle [Verfasser]; Lippuner, Claudia [Verfasser]; Schuster, Torben [Verfasser]; Gramlinger, Franz [Verfasser] (My University, 2021)
This chapter "reflects on the issue of excellence in VET by focusing on apprenticeship systems and specific initiatives in Austria, Denmark, Germany and Switzerland, asking whether and why, or to what extent, they might emphasise excellence. All four countries have a long tradition in establishing and developing their apprenticeship system, with a collective skill formation approach and strong decentralised governance modes. The four VET systems, nevertheless, represent differences in terms of governance that mirror the design and purpose of their concepts and initiatives for VET development. Hence, they are explicitly developing initiatives for promoting excellence in VET to varying extents. The main part of this contribution relies on a review of VET policy developments in Austria, Denmark, Germany and Switzerland. The conclusion of the reflection addresses the meaning of excellence in the apprenticeship concept over the range of qualifications offered by country-specific education systems, its characteristics, normative-prescriptive grade and (potential) impact; it also considers the links between the concepts of excellence, accountability and inclusiveness in education. The closing part of the contribution hints at the dilemma the excellence concept might bring into apprenticeship systems at national and possibly European level." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; L 6 Qualität; S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; I 2.1 Deutschland; I 2.2.1 Westeuropa; 370; Berufsbildungssystem; Attraktivität; Qualität; Berufsbildungspolitik; Governance; Internationaler Vergleich; Fallbeispiel; Europa; Bundesrepublik Deutschland; Dänemark; Österreich; Schweiz